2022
DOI: 10.1088/1752-7163/ac522f
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary method for profiling volatile organic compounds in breath that correlate with pulmonary function and other clinical traits of subjects diagnosed with cystic fibrosis: a pilot study

Abstract: Cystic fibrosis (CF) is characterized by chronic respiratory infections which progressively decrease lung function over time. Affected individuals experience episodes of intensified respiratory symptoms called pulmonary exacerbations (PEx) which accelerate pulmonary function decline and decrease survival. There is no standard classification for PEx, which results in treatments that are heterogeneous. Improving PEx classification and management is a significant priority for people with CF. Previous studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…A few VOCs normalised after one month mirroring a short-term impact of the treatment, whilst others progressed more slowly possibly indicating a delayed effect. Furthermore, the evolution of several breath VOCs correlated with clinical outcomes which builds upon recent findings by Woollam et al Using GC-MS, they identified a set of VOCs correlating with ppFEV1 in CF patients experiencing pulmonary exacerbations [30]. In our study, eight VOCs significantly modified upon treatment were also consistently (at both V2 and V3) associated with variations in lung function (ppFEV1 or ppFVC).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A few VOCs normalised after one month mirroring a short-term impact of the treatment, whilst others progressed more slowly possibly indicating a delayed effect. Furthermore, the evolution of several breath VOCs correlated with clinical outcomes which builds upon recent findings by Woollam et al Using GC-MS, they identified a set of VOCs correlating with ppFEV1 in CF patients experiencing pulmonary exacerbations [30]. In our study, eight VOCs significantly modified upon treatment were also consistently (at both V2 and V3) associated with variations in lung function (ppFEV1 or ppFVC).…”
Section: Discussionsupporting
confidence: 85%
“…These belong to the large range of carbonyl compounds that can be generated through lipid peroxidation, and which have been repeatedly associated with oxidative stress [33]. Woollam et al also observed a downregulation of longer aldehydes (octanal and nonanal) in patients treated with CFTR modulators [30]. Another significant VOC, dimethylformamide has been recently associated with dysfunctions in mitochondria [34] and glucose metabolism [35].…”
Section: Discussionmentioning
confidence: 99%
“…However, no single VOC was found significantly altered when applying UVA between stable and CF PEx patients. Meanwhile, Woollam et al (2022b) divided the CF patients into CF baseline (not suffering from PEx) and CF PEx. Four VOCs were found to be correlated with FEV1pp at the time of breath collection, of which two VOCs (4-methyl-octane and 3,7-dimethyldecane) were further correlated with changes in FEV1pp.…”
Section: Vocs In Exhaled Breath In Health and Pathologymentioning
confidence: 99%
“…Most studies were based on a paediatric population ( n = 16), and in 11 cases, adults were excluded. Four articles reported on exhaled VOCs measured with GC-MS [ 13 , 14 , 15 , 16 ], two papers concerned eNose-driven work [ 17 , 18 ] and one manuscript was focused on hydrogen cyanide in exhaled breath [ 19 ]. Biomarkers in exhaled breath condensate were measured in 11 studies.…”
Section: Resultsmentioning
confidence: 99%